The mutation of a PECTATE LYASE-LIKE gene is responsible for the Yellow Margin phenotype in potato - Yang, Z.; Feng, S.; Tang, D.; Zhang, L.; Li, Y.; Kear, P.; Huang, S.; Zhang, C. (Springer, 2020)
The practice of clonally propagating potato (Solanum tuberosum L.), which has been lasted for thousands of years, has caused the accumulation of deleterious alleles. Despite yellow margin (ym) being a common cause of a detrimental weak-vigor phenotype and reduced yield in diploid potato, the underlying gene has eluded discovery to date. In this paper, we mapped the ym gene to a 30-kb region containing four annotated genes. Among them, PGSC0003DMG402023481 encodes a pectate lyase-like gene (StPLL) with lower expression in ym plants than in the wild-type plants. PCR amplification confirmed a 4.1-kb deletion in the mutant allele of StPLL. Knockout of StPLL in diploid potato resulted in a similar phenotype with the ym plants. This study not only characterizes the ym allele but also provides the molecular tools to select and purge it from populations, while also deepening our understanding of the morphogenesis in potato.